Double percutaneous transesophageal gastrotubing precluded high risk surgery for intestinal malignant lymphoma. (April 2021) - Takeuchi, Hideyuki; Kamada, Teppei; Ohdaira, Hironori; Takahashi, Junji; Nakashima, Keigo; Nakaseko, Yuichi; Yoshida, Masashi; Okada, Shinya; Yamanouchi, Eigoro; Suzuki, Yutaka
Abstract: Primary gastrointestinal lymphoma is relatively rare and typically treated by chemotherapy. In some cases, surgery for obstruction in the proximal small intestine is challenging and has a high risk for anastomotic leakage. An 80-year-old woman presented to our hospital with vomiting and abdominal distension. Enteroscopy showed a type 2 circumferential tumor in the proximal jejunum 6 cm on the anal side from Treitz ligament. Biopsy showed solid and diffuse proliferation of large atypical cells with round and irregular nuclei. On immunohistochemistry, these cells were positive for CD20, CD79a, and CD138. Diffuse large B-cell lymphoma (DLBCL) was diagnosed and classified as Ann Arbor stage IIE and Lugano classification stage II 2 and scored 1 point on the International Prognostic Index (i.e., low risk). Given the risk of anastomotic leakage due to lesions and residual obstructive enteritis, surgery was not performed. The patient received double percutaneous transesophageal gastrotubing (dPTEG) to facilitate decompression and enteral nutrition. Enteral nutrition and chemotherapy were initiated immediately after dPTEG insertion. After one course of rituximab plus cyclophosphamide, hydroxydaunorubicin, oncovin, and prednisone (R–CHOP), the tumor showed a partial response, and the obstruction was improved. Oral ingestion was started, and the dPTEG tube was removed. After six courses of R–CHOP, enhanced CT, positron emission tomography-CT, and serum interleukin-2 levels indicated complete treatment response. During treatment, gastrointestinal perforation did not occur, oral intake was good, and careful follow-up will be continued. dPTEG for obstructive small intestinal DLBCL could help avoid high-risk surgery, and a complete response to chemotherapy was achieved. Highlights: ・Surgery for obstruction in the proximal small intestine is challenging and has a high risk for anastomotic leakage. ・Double percutaneous transesophageal gastrotubing is a novel treatment that can achieve both intestinal decompression and enteral nutrition. ・Performing dPTEG for obstructive small intestinal DLBCL precluded the use of high-risk surgery and facilitated a complete response to chemotherapy.